The knight's runaway maiden - Locke, Nicole (Locke, Nicole. Lovers and legends., 2021)
Balthus of Warstone secretly loved Séverine, even though she was unhappily married to his brute of a brother, then she fled six years ago. Now that her husband is dead, Balthus must find Séverine and reclaim her sons as his father's heirs. Balthus's desire is to claim her, too, and despite his battle-maimed arm and her distrust of his family, he'll prove he's a suitor worthy of such a courageous woman.